The conceptual sphere of the modern English pedagogical discourse - Nersesyan Gayane R. (Актуальные проблемы филологии и педагогической лингвистики, 2020)
The given article investigates the conceptual sphere of the modern English pedagogical discourse. The purpose of the paper is presented by the identification of the main concepts of discourse and the ways they are verbalised by means of language. In order to meet the aim the author touches upon the main approaches to the notion “concept”, as well as the concepts already identified in the pedagogical discourse. The main research is represented by the linguacognitive, pragma-semantic, and discourse analyses of the English pedagogical discourse, represented by the authentic pedagogical articles, along with the identification of its main concepts which reflect a wide range of both social and pedagogical processes. The results of the analysis represent the English pedagogical discourse to be rather independent conceptual sphere showing its own features. The identified concepts TOLERANCE, MULTICULTURALISM, PROFICIENCY and LANGUAGE show the strong interconnection between current social phenomena and the pedagogical sphere affecting the way individuals explore the world. The actualization of these concepts becomes possible with the help of language that implements dominant lexemes, derivatives, synonyms, evaluation, and other language means to deliver the functional role of the English pedagogical discourse. The research allows us to conclude that this very type of the discourse, its conceptual sphere and complex pragmatic-communicative charge still represent a wide scope for further research that is yet to be conducted.